2015
DOI: 10.1185/03007995.2015.1014029
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the use of administrative claims databases in conducting clinical real-world evidence studies in multiple sclerosis

Abstract: The methods suggested in this study offer a good foundation for performing real-world research in MS using administrative claims databases, potentially allowing evidence from different studies to be compared and combined more systematically than in current research practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 26 publications
(35 reference statements)
1
21
0
1
Order By: Relevance
“…Previous studies have reported that a 4-year history is insufficient to accurately classify MS patients as incident on the basis of claims data [21]. …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that a 4-year history is insufficient to accurately classify MS patients as incident on the basis of claims data [21]. …”
Section: Discussionmentioning
confidence: 99%
“…The Truven Health MarketScan® Commercial Claims and Encounters and Medicare Supplemental Research databases were used for the analysis. The databases combines data from >130 million inpatients and outpatients, linking paid claims and encounter data to detailed patient information across locations and types of providers and over time.…”
Section: Methodsmentioning
confidence: 99%
“…Electronic health record (EHR) databases are being used increasingly in the study of MS and its management [9]. MS subtype is clinically relevant for treatment and health care utilization decision making.…”
Section: Introductionmentioning
confidence: 99%